(5u-7x+2)(7u-6)=0

Simple and best practice solution for (5u-7x+2)(7u-6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5u-7x+2)(7u-6)=0 equation:


Simplifying
(5u + -7x + 2)(7u + -6) = 0

Reorder the terms:
(2 + 5u + -7x)(7u + -6) = 0

Reorder the terms:
(2 + 5u + -7x)(-6 + 7u) = 0

Multiply (2 + 5u + -7x) * (-6 + 7u)
(2(-6 + 7u) + 5u * (-6 + 7u) + -7x * (-6 + 7u)) = 0
((-6 * 2 + 7u * 2) + 5u * (-6 + 7u) + -7x * (-6 + 7u)) = 0
((-12 + 14u) + 5u * (-6 + 7u) + -7x * (-6 + 7u)) = 0
(-12 + 14u + (-6 * 5u + 7u * 5u) + -7x * (-6 + 7u)) = 0
(-12 + 14u + (-30u + 35u2) + -7x * (-6 + 7u)) = 0
(-12 + 14u + -30u + 35u2 + (-6 * -7x + 7u * -7x)) = 0

Reorder the terms:
(-12 + 14u + -30u + 35u2 + (-49ux + 42x)) = 0
(-12 + 14u + -30u + 35u2 + (-49ux + 42x)) = 0

Reorder the terms:
(-12 + 14u + -30u + -49ux + 35u2 + 42x) = 0

Combine like terms: 14u + -30u = -16u
(-12 + -16u + -49ux + 35u2 + 42x) = 0

Solving
-12 + -16u + -49ux + 35u2 + 42x = 0

Solving for variable 'u'.

The solution to this equation could not be determined.

See similar equations:

| -13u-3=4u^2 | | 6-37=n | | 5x-60=4+x | | f(x)=2r^2+2r-1 | | 4.11x-5.8(x-1.468)=6.2667 | | 2v-2v+v+3=7 | | 2(7c+1)-27=11c+2 | | 18.75=2x^3-x^2-14x | | -8a-(-11a)=-15 | | Y+2x^2=12+x | | 2(z+4)=-10 | | 8x+8=5x+2 | | 4354674563566465465x=63646675464435635534 | | 16/y=4 | | x+3(x-3)=2(x-5)-3 | | 0=-2(q+1) | | 3k-k-k-1=7 | | 0=7(7+8k)+3(k+5) | | 2(j-12)-(-9)=19 | | 6d-3(d-18)=6(d+9) | | 4w-2w=-16 | | ((21x)/(4-2x)/(3/(49-x^2))) | | 5(x-3)=180/12 | | 4-u=3 | | 15.5w=-204.6 | | -4t-8t=12 | | -30-25v=9v^2 | | -6(n+4)+25=-3n-11 | | 8m-16=-21+7m | | 4s-20=-5+s | | (2i)(-i)+(6i)= | | 14-(x+1)=4(x+4) |

Equations solver categories